2020
DOI: 10.1093/brain/awaa171
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy subtype-specific copy number burden observed in a genome-wide study of 17 458 subjects

Abstract: Cytogenic testing is routinely applied in most neurological centres for severe paediatric epilepsies. However, which characteristics of copy number variants (CNVs) confer most epilepsy risk and which epilepsy subtypes carry the most CNV burden, have not been explored on a genome-wide scale. Here, we present the largest CNV investigation in epilepsy to date with 10 712 European epilepsy cases and 6746 ancestry-matched controls. Patients with genetic generalized epilepsy, lesional focal epilepsy, non-acquired fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 61 publications
5
43
1
1
Order By: Relevance
“…Recently we showed that genomic DNA methylation signatures also distinguished major FCD subtypes from TLE patients and non-epileptic controls [36]. Here, we confirmed and developmental, behavioral, and psychiatric problems (e.g., autism spectrum disorders, attention-deficit disorder, learning disabilities, schizophrenia), and seizures [14,24,48,52].…”
supporting
confidence: 73%
“…Recently we showed that genomic DNA methylation signatures also distinguished major FCD subtypes from TLE patients and non-epileptic controls [36]. Here, we confirmed and developmental, behavioral, and psychiatric problems (e.g., autism spectrum disorders, attention-deficit disorder, learning disabilities, schizophrenia), and seizures [14,24,48,52].…”
supporting
confidence: 73%
“…This number does not include the potentially toxic sSNVs in non‐coding parts of the genome that have also been linked to neurodevelopmental disorders such as autism (34, 38–43). Nor does it take into account the effect of somatic structural variants such CNVs that are known causes of focal epilepsies (44, 45). In other words, the contribution of somatic variants to focal epilepsies is likely more far‐reaching than what is known to date.…”
Section: Somatic Mosaicism In Focal Epilepsies and The Need For Single Cell Genomic Approachesmentioning
confidence: 99%
“…This manifold of diseases highlights the central role of genes on the long arm of chromosome 1 in overall development, but also brain structure and function. For example, recurrent rearrangements of 1q21.1 are associated with microcephaly or macrocephaly, developmental, behavioral, and psychiatric problems (e.g., autism spectrum disorders, attention-deficit disorder, learning disabilities, schizophrenia), and seizures [ 14 , 25 , 49 , 53 ]. 1q24 deletions cause a phenotype of intellectual disability, growth retardation, microcephaly, and facial dysmorphism [ 17 ].…”
Section: Discussionmentioning
confidence: 99%